The relationship between leadership styles and employees job engagement in service logistic company - Haridas, Sathiarooban (2019)
Employees are the most important asset of an organization as they are the ones that decides the success or failure of the organization. Apart from this consideration, leadership style is also expected to play a significant role in determining the employees’ engagement. This study is intended to investigate the relationship between of leadership styles, particularly the relationship of transformational, transactional and laissez-faire leadership style and employee job engagement. Total of 200 sets of questionnaires were distributed to the employees of the service logistic company and 161 sets of questionnaires successfully being collected from the respondents. Descriptive analysis used to understand the respondents demographic information otherwise inferential analysis used to discover the relationship between independent variable such transformational , transactional and laissez-faire leadership style and dependent variable which is the employee job engagement.According to the study conducted, transformational leaders are those “outstanding” individuals that have the ability to obtain their employees’ job engagement, intellectually boost them and strategically drive them with the vision and mission of the organization. In adverse to this, is transactional leadership which is basically an exchange relationship between the leader and employee whereby the leader exchanges rewards and/or incentives for performance has no relationship with employees job engagement. Meanwhile, Laissez-faire is the less frequent leadership style that has the greatest negative effect on employees job engagement. Employees were found entirely disengaged when Laissez-faire leadership style being projected.Besides that, this study added to existing literature by channeling idea into the strength and direction of relationships among these variables.